Phylogenetic position of Aerumnosa Mohrig (Diptera, Sciaridae) as revealed by multigene analysis, with the description of four new Oriental species - Vilkamaa, Pekka; Rudzinski, Hans-Georg; Burdíková, Nikola; Ševčík, Jan (Zootaxa, 2018)
Four Oriental species of Aerumnosa Mohrig, 1999 (Diptera: Sciaridae), a genus previously known only from Papua New Guinea, are newly described and illustrated: Aerumnosa bituberculata sp. n. (India), A. gemmifera sp. n. (Malaysia: Sabah), A. horrifica sp. n. (Brunei, Thailand) and A. impar sp. n. (Malaysia: Sabah). On the basis of the new material, the genus is redefined. A key to the known species of Aerumnosa is presented, including four new species. An updated molecular phylogenetic analysis based on four gene markers (18S, 28S, 16S and COI) shows Aerumnosa to be a member of the subfamily Cratyninae. The monophyly of Cratyninae is well supported, which clade also includes the genera Hyperlasion Schmitz, 1919, Pnyxiopalpus Vilkamaa & Hippa, 1999 and Pseudoaerumnosa Rudzinski, 2006. According to the present phylogenetic hypothesis, the monophyly of Cratyna Winnertz, 1967 s. l. needs to be revisited. The clade including Cratyna (s. str.) ambigua (Lengersdorf, 1934) appears as the sister group of Aerumnosa.